SCIENTIFIC PROGRESS AND PERSPECTIVES OF CHILDREN’S HEMATOLOGY/ONCOLOGY DEVELOPMENT - A.G. Rumyantsev (Вопросы современной педиатрии, 2010)
Progress of biology leading to the decoding of genome and forming of post-genome cell regulation of human development, resulted in separation of new pediatric speciality: children’s hematologist/oncologist. Clinical studies in children’s hematology/oncology are dedicated to study of pathogenesis and development of scientifically-based methods of diagnostics and treatment of hereditary and obtained diseases of blood and immune system, oncological diseases of newborns, children and adolescents. Interdisciplinary approach in science and organization of service in children’s hematology/oncology departments on the basis of multisectoral children’s hospitals led to significant results. The article presents most significant scientific and practical achievements of Russian scientists and doctors in diagnostics and treatment of hematological and oncological diseases in children and adolescents.Key words: children’s hematology, immunology, oncology.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):7-15)